2014
DOI: 10.1177/0038038513516694
|View full text |Cite
|
Sign up to set email alerts
|

A Sociologist Walks into a Bar (and Other Academic Challenges): Towards a Methodology of Humour

Abstract: Humour and laughter have been regarded as suitable topics for research in the social sciences, but as methodological principles to be adopted in carrying out and representing the findings of research they have been neglected. Indeed, those scholars who have made use of humour – wit, satire, jokes etc. – risk being regarded as trivial and marginalised from the mainstream. Yet, in literature the idea that comedy can tell us something important about the human condition is widely recognised. This neglect of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 42 publications
0
61
0
3
Order By: Relevance
“…Telling jokes and stories about fines, bureaucracy, scientists or seals can be ways to lighten or dismiss the demands and burdens involved in everyday work. It has been observed that all forms of work involve such coping mechanisms (Dean et al 1998;Holmes 2000;Morreall 2011;Watson 2015). This means that the subjects of jokes and cynicism are not always and ultimately considered as unacceptable or illegitimate.…”
Section: Methodological Challengesmentioning
confidence: 99%
“…Telling jokes and stories about fines, bureaucracy, scientists or seals can be ways to lighten or dismiss the demands and burdens involved in everyday work. It has been observed that all forms of work involve such coping mechanisms (Dean et al 1998;Holmes 2000;Morreall 2011;Watson 2015). This means that the subjects of jokes and cynicism are not always and ultimately considered as unacceptable or illegitimate.…”
Section: Methodological Challengesmentioning
confidence: 99%
“…We could speculate that these rules attempt to create a pseudo-professional community rather than use reddit to widely disseminate scientific information -a view certainly felt by other corners of the internet, and by other reddit users who have created explicitly more informal alternatives. 8 This would tally with arguments that academics often try to minimise humour in written communication in order to preserve an image of detachment and professionalism [Heard, 2014;Watson, 2015].…”
Section: Redditmentioning
confidence: 99%
“…The import of such a research agenda for the future direction of humour studies in sport should be clear as we touch upon the subtleties of humour (Watson, 2015). It appears that humour is neither 'trivial' nor 'playful' in the negative, and yet we cannot ignore how it has been used here in a plethora of ways to act as resistance to racism in sport.…”
Section: Resultsmentioning
confidence: 99%